1999
DOI: 10.1038/16717
|View full text |Cite
|
Sign up to set email alerts
|

ICOS is an inducible T-cell co-stimulator structurally and functionally related to CD28

Abstract: The T-cell-specific cell-surface receptors CD28 and CTLA-4 are important regulators of the immune system. CD28 potently enhances those T-cell functions that are essential for an effective antigen-specific immune response, and the homologous CTLA-4 counterbalances the CD28-mediated signals and thus prevents an otherwise fatal overstimulation of the lymphoid system. Here we report the identification of a third member of this family of molecules, inducible co-stimulator (ICOS), which is a homodimeric protein of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
375
0
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,302 publications
(386 citation statements)
references
References 29 publications
8
375
0
3
Order By: Relevance
“…Triggering of ICOS by ICOS-L expressed by EC had a profound effect on the secretion of Th1 as well as Th2 cytokines, a finding that corroborates the hypothesis that ICOS͞ICOS-L does not only have a role in the control of Th2, but might also have a critical function in the control of Th1 immune responses (38). On the basis of previous data, we and others suggested a model in which CD28 costimulates primary T cell functions, whereas ICOS plays a more prominent role in the costimulation of effector or memory T cell responses (10,39). Our functional data presented here are in agreement with such a concept.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Triggering of ICOS by ICOS-L expressed by EC had a profound effect on the secretion of Th1 as well as Th2 cytokines, a finding that corroborates the hypothesis that ICOS͞ICOS-L does not only have a role in the control of Th2, but might also have a critical function in the control of Th1 immune responses (38). On the basis of previous data, we and others suggested a model in which CD28 costimulates primary T cell functions, whereas ICOS plays a more prominent role in the costimulation of effector or memory T cell responses (10,39). Our functional data presented here are in agreement with such a concept.…”
Section: Discussionsupporting
confidence: 68%
“…8 and 9). Instead, ICOS-L binds to ICOS, a T cell-specific costimulatory molecule homologous to CD28 and CTLA-4 (8)(9)(10). The strong impact of ICOS͞ICOS-L interaction on T cell-mediated immune responses in vivo became evident by the disruption of the ICOS gene in mice.…”
Section: Nducible Costimulator-ligand (Icos-l) Is a Member Of The B7mentioning
confidence: 99%
“…It has been suggested that stimulation of ICOS on CD4 ϩ T cells preferentially promotes IL-10 production (23,32,33). Moreover, the importance of the ICOS molecule in IL-10-producing Tr cells was reported in respiratory tolerance (25).…”
Section: Icos Expression Is Highly Correlated With Il-10 Production Imentioning
confidence: 99%
“…A new member of the CD28 family, inducible costimulator (ICOS) is a T cell-specific cell-surface molecule structurally related to CD28 and cytotoxic T lymphocyte-associated antigen 4 (23,24). Both CD28 and ICOS molecules are able to amplify the secretion of several cytokines, but only CD28 induces substantial amounts of IL-2, whereas ICOS shows a certain preference for the induction of IL-10 (23).…”
mentioning
confidence: 99%
“…Current models suggest that greater CD28 signal can achieve Th2 differentiation (6,7). An inducible costimulator, ICOS, also called H4 (8,9) or AILIM (10), is a member of the CD28 family and has roles similar to those of CD28 except for IL-2 production (11)(12)(13). Accumulating evidence indicates a predominant role of ICOS in Th2-type immune responses, as exemplified by its promoting effect on Th2 cell differentiation, concomitant cytokine secretion, airway hypersensitivity reaction, and Igclass switching (14 -17).…”
mentioning
confidence: 99%